1995
DOI: 10.2166/wst.1995.0276
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and modelling the kinetics in a full scale submerged denitrification filter

Abstract: Experimental data in forms of vertical concentration profiles has been provided from a full scale submerged denitrification filter with biocarbone as filter material. Denitrification rates were determined in full scale under different loads of nitrate and methanol with methanol in excess. Vertical concentration profiles of nitrate and methanol have verified kinetics in the half-order region with removal rate constants in the range of k0.5A = 0.13-0.21 g N0.5 m−0.5 d−1 (0.5 order for partial pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Consequently, full-scale implementation of heterotrophic denitrification is still guided by a somewhat empirical understanding of its microbial ecology and biokinetics, which in turn limits efforts to optimize denitrification reactor design, monitoring and modeling. Although biokinetic parameters for methylotrophic denitrification in activated sludge have been extensively reported (dos Santos et al, 2004;Gauntlett, 1979;Her and Huang, 1995;Janning et al, 1995;Lee and Welander, 1996;Louzeiro et al, 2002;Mulcahy et al, 1981;Purtschert and Gujer, 1999), the actual abundance and diversity of organisms in activated sludge that actually metabolize methanol and alternate carbon and electron sources has only recently been identified (Ginige et al, 2004(Ginige et al, , 2005Osaka et al, 2006Osaka et al, , 2008. The reason for such sparse data on the identity of bacterial populations denitrifying using specific electron donors is that unlike nitrifying bacteria, which are phylogenetically closely related (Purkhold et al, 2000), denitrifying bacteria are distributed widely across taxonomic groups (Zumft, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, full-scale implementation of heterotrophic denitrification is still guided by a somewhat empirical understanding of its microbial ecology and biokinetics, which in turn limits efforts to optimize denitrification reactor design, monitoring and modeling. Although biokinetic parameters for methylotrophic denitrification in activated sludge have been extensively reported (dos Santos et al, 2004;Gauntlett, 1979;Her and Huang, 1995;Janning et al, 1995;Lee and Welander, 1996;Louzeiro et al, 2002;Mulcahy et al, 1981;Purtschert and Gujer, 1999), the actual abundance and diversity of organisms in activated sludge that actually metabolize methanol and alternate carbon and electron sources has only recently been identified (Ginige et al, 2004(Ginige et al, , 2005Osaka et al, 2006Osaka et al, , 2008. The reason for such sparse data on the identity of bacterial populations denitrifying using specific electron donors is that unlike nitrifying bacteria, which are phylogenetically closely related (Purkhold et al, 2000), denitrifying bacteria are distributed widely across taxonomic groups (Zumft, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Zero-order heterogeneous reactions in a pore that is only partially penetrated by the substrate result in half-order reaction kinetics for nitrate concentration. Half-order reaction kinetics result in the following expressions for a plug flow reactor (Harremoes, 1976;Hultman et al, 1994): Profile sampling conducted at different media depths by Harremoes (1976), Hultman et al (1994), and Janning et al (1995) have shown the half-order kinetic model reasonably correlates to observed values. Half order kinetic constants of 0.25 to 0.9 for temperatures ranging form 6 to 19 0C were reported by Harremoes (1976).…”
Section: Tertiary Denitrificationmentioning
confidence: 99%
“…Wastewater flow along the biofilter depth could be considered as a plug flow, and denitrification could be described with a half-order reaction as follows [27]. [28] found that the half-order coefficient increased with increasing the initial nitrate concentrations. This might be one of the reasons responsible for the increased half-order coefficient at the EBRT of 7.5 min in DNBF S , where the initial nitrate concentration was relatively high.…”
Section: Dynamics Of Oxidized Nitrogen Along the Biofilter Depthmentioning
confidence: 99%